2007
DOI: 10.1016/j.jhsb.2007.02.005
|View full text |Cite
|
Sign up to set email alerts
|

To Suspend or not to Suspend: A Randomised Single Blind Trial of Simple Trapeziectomy Versus Trapeziectomy and Flexor Carpi Radialis Suspension

Abstract: The thumb carpometacarpal joint is the second most common site of osteoarthritis in humans. There are numerous operations for the condition but, perhaps, the commonest is trapeziectomy, sometimes supplemented by a suspension procedure, most commonly using part of the flexor carpi radialis tendon. In order to determine whether there is an advantage to a suspension procedure, or not, 65 patients with Eaton and Glickel Grade III or IV arthritis of the carpometacarpal joint of their thumbs were randomised into eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
119
2
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(141 citation statements)
references
References 21 publications
(36 reference statements)
8
119
2
10
Order By: Relevance
“…Estudos comparativos entre a trapeziectomia com e sem ligamentoplastia sugerem que não há benefícios de uma técnica sobre outra (2)(3)(20)(21) . Embora vários recursos tenham sido tentados para evitar a migração do 1 o metacarpiano após a remoção do trapézio, como a ligamentoplastia ou suspensão, fixação com fios de Kirschner ou imobilização pós-operatória prolongada, nenhum deles manteve a altura do espaço original entre a base do 1 o metacarpiano e o escafóide.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Estudos comparativos entre a trapeziectomia com e sem ligamentoplastia sugerem que não há benefícios de uma técnica sobre outra (2)(3)(20)(21) . Embora vários recursos tenham sido tentados para evitar a migração do 1 o metacarpiano após a remoção do trapézio, como a ligamentoplastia ou suspensão, fixação com fios de Kirschner ou imobilização pós-operatória prolongada, nenhum deles manteve a altura do espaço original entre a base do 1 o metacarpiano e o escafóide.…”
Section: Discussionunclassified
“…Esse mesmo achado foi observado por Field et al quando compararam o resultado da trapeziectomia simples com a trapeziectomia e ligamentoplastia (20) , embora o tempo de seguimento de seus pacientes tenha sido de apenas 12 meses. Também Davis et al não acharam diferença significativa de força de preensão e de pinça quando compararam três grupos de tratamento: trapeziectomia simples, trapeziectomia com interposição tendinosa e trapeziectomia com ligamentoplastia.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The overall complication rate for trapeziometacarpal surgery is high and one of the possible complications is CRPS (variable incidence of 8 to 19 %) [17,21]. Torrededia et al described 5 cases of CRPS after 38 operations (13%) with the same implant we used, but under vitamin C we detected no CRPS in our study group [22].…”
Section: Resultsmentioning
confidence: 58%
“…Field et al reported complex regional pain syndrome type I in 8% after ligament reconstruction and tendon interposition [21].…”
Section: Discussionmentioning
confidence: 99%